A difusão da acessibilidade às energias alternativas eólica e solar e o efeito na arrecadação tributária ICMS no Estado do Ceará - Silveira, Erasmo Augusto de Azevedo (2012)
The necessity to find alternative paths to the problem of non-renewable energy and harmful to the environment is a prerequisite for sustainable development. The state of Ceará has proven by studies, wide-ranging impact of alternative energy sources and solar wind to be used. The possibility of changing the profile of generation and consumption of the energy matrix with the largest share of these is possible and beneficial. In this surround this core profile change in tax collection of the ICMS - Tax on Goods and Services in the state of Ceará, for the energy distribution of incidence is the same field. The main objectives will determine what impact this hypothetical tax revenues in the Electric Power Industry, specifically as to what is collected by the utility power distribution for consumption in our state, happen when there was the replacement / complement the energy used today by alternative wind and solar, with an increasing participation of those in the energy consumption in the State of Ceará. Secondly, as this would imply the total costs, taxes and other charges, ie, the overheads involved in the sector. The econometric method used was simple linear regression to estimate the variation of the generation cost of wind energy compared to the year and the amount of wind power generated. On result was found then the gradual decrease of this cost.